PENDAMPINGAN GURU DALAM PEMBELAJARAN BERBASIS PROYEK GUNA MENINGKATKAN HASIL BELAJAR DAN KETERAMPILAN MOTORIK HALUS PADA SISWA KELAS RENDAH SEKOLAH DASAR - Etika Ariyani,; Baiq Titik Hendrawati, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
The purpose of this community service program was to assisted teacher improve the students achievement and fine motor skills. These skill improved by creating greeting card using project based learning at low class. This investigation applied a classroom action research which consists of two cycles with four main steps such as planning, implementation, observation and reflection. Data collection procedures used test and observation, data analysis procedures such as data reduction, analysis and summarizing. The final result of this program shown that there is significant improvement at students achievement and their fine motor skills. At the first cycle, 78 % students achieved mastery learning then improved significantly to 88 % at second cycle. The score of students classroom activities at the first cycle 72.36 then elevated significantly to 86.03. Based on the result of this investigation, it can concluded that the implementation of project based learning can improved students achievement and fine motor skills significantly because the students score higher than standard of minimum completeness of mastery learning at low class of Elementary School